Morphologic and genic effects of waste pollution on the reproductive physiology of Paracentrotus lividus lmk: a mesocosm experiment - Glaviano, Francesca; Federico, Serena; Pinto, Bruno; Gharbi, Maissa; Russo, Tania; Cosmo, Anna Di; Polese, Gianluca; Costantini, Maria; Zupo, Valerio (Frontiers in Physiology, 2023)
A considerable amount of coastal contamination is caused by organic wastes, even if our attention is commonly focused on chemical pollutants and contaminants. Most organic pollutants are represented by highly dilute soluble compounds and particles deriving from dead organisms. This complex combination, consisting of suspended particles and dissolved macromolecules, has a significant impact on coastal planktonic and benthic organisms, also playing an active role in the global cycles of carbon. In addition, production practices are nowadays shifting towards recirculated aquaculture systems (RAS) and the genic responses of target organisms to the organic pollution are still scarcely addressed by scientific investigations. The reservoir of organic matter dissolved in the seawater is by far the least understood if compared to that on land, cause only a few compounds have been identified and their impacts on animals and plants are poorly understood. The tendency of these compounds to concentrate at interfaces facilitates the absorption of dissolved organic compound (DOC) onto suspended particles. Some DOC components are chemically combined with dissolved metals and form complexes, affecting the chemical properties of the seawater and the life of the coastal biota. In this research, we compared the reproductive performances of the common sea urchin Paracentrotus lividus cultured in open-cycle tanks to those cultured in a recirculating aquaculture system (RAS), where organic pollution progressively increased during the experiment, even not reaching deadly concentrations. Sea urchins were cultured for seven months under these two conditions and their gametes were collected. Embryos resulting by in vitro fertilization were analyzed by Real Time qPCR to identify possible effects of pollution-induced stress. The fertility of sea urchins was evaluated, as well as the gonadosomatic indices and the histological features of gonads. Our results indicate that organic pollution, event at sub-lethal concentrations, may hardly impact the reproductive potential of this key species and that chronic effects of stress are revealed by the analyses of survival rates and gene expression.